Distribution And Abundance Of Benthic Molluscs In Coastal Waters Of Northwestern Penang Island - Mustaffa, Alianie (2013)
The study was surveyed from October 2010 to September 2011 at four sampling sites—Teluk Bahang, Teluk Aling, Teluk Ketapang, and Pantai Acheh. At each site, benthic molluscs, sediments, and water quality parameters were sampled every 2 months, at intervals of 200 m with 6 sampling points. A total of 21 families, 21 genera, and 25 species were recorded with mean abundance of 613.6 molluscs/m2. The dominant species found in the present study were Sacella bellula, Nucula sp., Timoclea sp., Vaceuchelus sp., Ethaliella sp., Ringicula propiquans, Retusa sp., and Lucidesta sp. The highest species diversity (H’ = 1.58) and species dominance (D = 0.74) were recorded at Pantai Acheh; the highest species evenness was recorded at Teluk Aling (E=0.50); the highest total abundance (35,757.3 molluscs/m2) was observed at Teluk Bahang; and the highest organic matter (16.43%) was recorded at 200 m distance. The measured water quality parameters did not differ significantly among the 4 sampling sites (ANOVA, p > 0.05). The following mean values for water quality parameter were determined: nitrite, 0.015 ± 0.001 mg/L; nitrate, 0.01 ± 0.003 mg/L; ammonia, 0.02 ± 0.003 mg/L; orthophosphate, 0.12 ± 0.005 mg/L; total suspended solids (TSS), 138.66 ± 6.38 mg/L; dissolved oxygen, 5.21 ± 0.08 mg/L; pH, 8.57 ± 0.01; salinity, 29.52 ± 0.08‰, and temperature, 29.97 ± 0.05°C. Cluster analysis with Ward’s method (Tukey’s test, p < 0.05) revealed the presence of 3 main groups based on particle size distribution, organic matter content, pH value, ammonia concentration, and distribution and abundance of benthic molluscs.